Peran Keluarga dalam Mendorong Kualitas Pembelajaran di Sekolah menurut konsep Ki Hadjar Dewantara dan Romo Mangun - A., La Ali Dono; Kusumawati, Intan (Academy of Social Science and Global Citizenship Journal, 2021)
The background of this research is a study that tries to explore the role of the family in encouraging the quality of learning in schools according to the concept of Ki Hadjar Deawantara and Romo Mangun. The two ideas of educational figures that are presented in this simple work are recognized as being able to answer the challenges of implementing contemporary education which is considered to be far from the expectations of the community. Where the implementation of education is still carried out mechanically which is proven to distance students from their culture and the management of education is carried out with the principle of profit oriented (seeking profit). The type of research used in this study uses a library research approach . The data collection technique in this study is a library through written sources such as books, journals, research reports, and sources from the internet. Meanwhile, the data analysis technique used in this study is descriptive analysis. The results of this study include the following: First, Ki Hadjar Dewantara, the idea of educational thinking is oriented towards the principle of human independence, students Given freedom in recognizing its culture, and the principle of togetherness. Second, Romo Mangun, emphasized the importance of education oriented towards humanizing the implementation of education with the concept of Basic Education Dynamics (BED) and equipping small communities and groups weak to recognize his right in education. Third, the relevance of the educational ideas of Ki Hadjar Dewantara and Romo Mangun to the current implementation of education, namely that the current management of education runs without clear orientation and tends to be profit oriented without regard to clear out puts. As a result, out put education cannot answer the needs of learners and relatively distances students from their culture and education can exploit its learners. Therefore , it is important that the educational concept of Ki Hadjar Dewantara and Romo Mangun be reapplied to overcome current educational problems. The suggestions in this study are as follows : (1) The design of education policies before they are implemented must pass the socialization stage with the parents of students or the community so that the community moreover, parents of students can understand the purpose and objectives of the policy, (2) The management of learning as much as possible must involve the parents of students such as determining the determination of strategic decisions relating to the future of learners, (3) The implementation of learning in schools should be free from discriminatory practices and forms of injustice , distancing students from their environment, (4) Cooperation between school management and parents of students must continue to be improved so that there is synergy between schools with parents of students in improving the growth and development of students both in the school environment and outside the school.